A Mechanism For Women Safety With Help Of Iot And Smart Devices - et. al., Palvadi Srinivas Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Day by day the girl, sister, mother etc., were facing the lot of challenges in the outside environment in protecting themselves. They were facing many challenges daily basis. Due to secure them by the help of Internet of things (IoT) we have brought up an wearable gadget for making them more secure so that by help of that device they can alert them to the nearest police station, known people, they can trace their location etc., we have brought up this technique whenever they can make use of this device whenever they feel unsafe. We have implemented our work with the help of Microcontroller named STM32F407VG which is a 64 bit Micro-Controller, WI-FI, BLE. Here by help of various geo-graphical devices which are linked to the device can easily identify the location of the person.